2021
DOI: 10.2147/jep.s255209
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Pharmacotherapy for COVID-19: The Latest Advances

Abstract: The coronavirus infectious disease-2019 (COVID-19) has overwhelmed like a shock wave in a completely unprepared world. Despite coronavirus infections were involved in previous epidemic outbreaks, no antiviral agent was developed for specific treatment. As a consequence, since the beginning of this pandemic, both repositioned and experimental drugs were used to treat the infected patients without evidence of clinical efficacy. Just based on experience coming from the use of antiviral agents to treat other virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 105 publications
0
26
0
Order By: Relevance
“…COVID-19 manifests a spectrum of signs and symptoms from mild illness to acute pneumonia. Unfortunately, a considerable percentage of patients rapidly worse to acute respiratory distress syndrome (ARDS) requiring intensive care ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 manifests a spectrum of signs and symptoms from mild illness to acute pneumonia. Unfortunately, a considerable percentage of patients rapidly worse to acute respiratory distress syndrome (ARDS) requiring intensive care ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Today most deaths due to COVID-19 are caused by respiratory failure (stage 3) from cytokine storms and there is no effective and specific treatment is not yet for all the stages. A limited effect on the early stages (stage 1-2) with antiviral agents such as remdesivir, favipiravir, darunavir, lopinavir/ritonavir has been shown besides with the randomized controlled studies still continue on (10). Stage 3 is related to cytokine release syndrome which demonstrates high levels of interleukins (IL) (IL-1 β, IL-1RA, IL-6, IL-8, IL-9, IL-10, IL-17), macrophage inflammatory protein, vascular endothelial growth factor, tumor necrosis factor-alpha (TNF-α), and other pro-inflammatory chemokines, cytokines, and signaling proteins (11).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the ACTT-1 trial (NCT04280705) showed that Remdesivir shortens the recovery time (median 11 days compared to 15 days in the placebo group) (52, 53) of ventilated COVID-19 patients and was granted EUA for use in severe COVID-19 patients in the US and the EU. Considering the results of other clinical studies, FDA gave full approval of Remdesivir for COVID-19 treatment a few month later in the US (52)(53)(54). However, the WHO SOLIDARITY study reported that Remdesivir had little or no effect on the length of hospitalization, transition to ventilation, or overall mortality and recommended against the use of it for COVID-19 treatment (55).…”
Section: Remdesivirmentioning
confidence: 99%